Impact of Using Alternative Graft Function Endpoints: A Secondary Analysis of a Kidney Transplant Trial. Issue 4 (April 2019) - Fergusson, Nicholas A.; Ramsay, Tim; Chassé, Michaël; English, Shane W.; Knoll, Greg A.
Abstract : Background: Nephrology trials assessing the impact of interventions on "standard" outcomes, such as doubling of creatinine, end-stage renal disease (ESRD), and/or death, are difficult to conduct given the time required for endpoints to accrue. The objective of this study was to determine if using lesser declines in kidney function would alter the interpretation of a previous randomized controlled trial. Methods: This study was a secondary analysis of a kidney transplant trial comparing the use of a 40% or greater, 30% or greater, or 20% or greater decline in estimated glomerular filtration rate (eGFR) as a substitute for doubling of serum creatinine. Declines in eGFR were determined relative to baseline. This trial enrolled 212 kidney transplant patients with proteinuria and assessed the clinical impact of ramipril versus placebo on a primary outcome of doubling of serum creatinine, ESRD, or death. In this analysis, the declines in eGFR replaced doubling of creatinine in the composite endpoint. Results: Mean trial follow-up was 41 months. A time-to-event composite of death, ESRD, or a 40% or greater, 30% or greater, or 20% or greater eGFR decline occurred in 45 (26 placebo vs 19 ramipril), 68 (35 vs 33), and 99 (50 vs 49) patients, respectively. Substituting these eGFR declines for doubling of serum creatinine resulted in an increase of 12, 35, and 66 endpoints compared with the original trial. In all 3 eGFR declines, ramipril treatment was not associated with any statistically significant differences despite the increase in events. Conclusions: Substituting doubling of serum creatinine for lesser eGFR percentage decline thresholds did not alter trial interpretation but did increase the number of events. Abstract : Supplemental digital content is available in the text.